The role of social media in the spread of health misinformation in South Africa: the Netwerk24 Facebook page, Afrikaner identity, and COVID-19 vaccine hesitancy - Davies-Laubscher, Nicola (Centre for Film and Media Studies, 2025)
The increase in health misinformation shared on social media resulted in the World Health Organisation declaring an ‘infodemic' (or information pandemic) during the early stage of the COVID-19 pandemic in 2020. Health misinformation can have serious consequences, including public resistance to health initiatives such as vaccine uptake and the endorsement of pseudoscientific health practices. This study uses qualitative content analysis and ethnographic methods to examine the comments of misinformation related to COVID-19 that were posted by White Afrikaans speakers (or Afrikaners) on the Netwerk24 Facebook Page during a two-year period of the pandemic spanning 1 March 2020 until 28 February 2022. Categorising the themes of misinformation shared among commentators, the study uses social identity theory and populism to explore the types of misinformation shared by Afrikaners on Facebook and seeks to determine how these comments of misinformation reflect the dominant markers of Afrikaner social identity. In recent years, misinformation shared via online platforms has been confounded by a global rise in populism, a political approach closely tied to social identity theory and the ways in which individuals derive a sense of self from their membership to different social groupings. This thesis explores how Afrikaners used the Netwerk24 Facebook Page to disseminate COVID-19 misinformation that mirrored populist trends in the United States under the presidency of Donald Trump. Using social identity theory, the study explores how the Afrikaners' group affiliations and perceptions of ‘us versus them' contributed to the formation and appeal of a growing populist narrative that emphasise the interests of a particular group over others. The decision to employ ethnography as the primary research methodology in this study came from recognising in the comments on the Netwerk24 Facebook Page the same dialogue that symbolised my upbringing in a conservative White Afrikaans society during apartheid. Being conscious of my own identity within the broader context of those participating in the comments section of the Netwerk24 Facebook Page afforded me unique insights into the participants' viewpoints, especially in how they relate to the concept of an Afrikaner identity.